Políticas culturais no Brasil contemporâneo: uma perspectiva econômica crítica de seus limites e possibilidades - Pacheco, Victor (2020)
The culture related themes have become recurrent in the last four decades, gaining worldwide relevance in the formulation of public policies. Therefore, this dissertation is dedicated to the analysis of the economic aspects of cultural policy in Brazil‘s contemporaneity. It is proposed, mainly, a critical reflection on the culture financing under the prism of the relations between State, market and cultural policy. In this context, the process of country‘s re-democratization throughout the 1980s brought a new perspective for the formulation and execution of public policies. The elaboration of a broad framework of universal rights became strong in the Constituent Assembly of 1988, founded on freedom of expression, essential for cultural production. On the other hand, the international context showed a predominance of ideas to reduce the State and expand mechanisms aimed at the market, in a movement supported by the Washington Consensus. With that said, the challenge of establishing a coherent set of public cultural policies emerges in the scenario after the censorship period of the military dictatorship to, from then on, subscribe to the market‘s pressures and logic as a criterion and condition. It is at this threshold that the relevant issues to the concept of culture and its consequences are discussed, in order to support the particular approach to the Brazilian case. The methodological elements are hybrid between the bibliographic and documentary character and the empirical analysis, based on interviews with agents and entities in the cultural field. The research seeks, founded on the assessment of the hypothesis that mediation between the State and the private sector achieved an insufficient logic for the financing of the discussed sector, to examine whether the change in posture of the state entity was also unsatisfactory for the significant and persistent change in the situation. Above all, the elements of the two major models for financing culture in Brazil are articulated: the tax incentive mechanism, under the symbol of the Rouanet Law, and the direct budget execution, represented by the Cultura Viva Program. The qualitative results of the research indicate that both models are in relative crisis, requiring reconsiderations about their designs, both on objective and subjective views